Fertility desires of people living with HIV: does the implementation of a sexual and reproductive health and HIV integration model change healthcare providers' attitudes and clients' desires? - Cecilia Milford; Mags Beksinska; Ross Greener; Jacqueline Pienaar; Letitia Rambally Greener; Zonke Mabude; Jennifer Smit (BMC, 2021)
Abstract Background There is a need for information and healthcare support for the fertility desires and contraceptive needs of people living with HIV (PLHIV) in order to provide safer conception support for sero-discordant couples wanting to safely conceive. A model to integrate sexual and reproductive health and HIV services was developed and implemented in a district hospital and six clinics in the eThekwini District, South Africa. Methods To evaluate the model's success, a cross-sectional survey was conducted before and after implementation of the model. As part of this evaluation, fertility desires of PLHIV (both male and female), and providers' perspectives thereof were explored. Changes in desires and attitudes after integration of services were investigated. Results Forty-six healthcare providers and 269 clients (48 male, 221 female) were surveyed at baseline, and 44 providers and 300 clients (70 male, 230 female) at endline. Various factors including relationship status, parity and antiretroviral treatment (ART) access influenced PLHIVs' desires for children. Concerns for their own and their child's health negatively impacted on PLHIV's fertility desires. These concerns declined after integration of services. Similarly, providers' concerns about PLHIV having children decreased after the implementation of the model. Conclusions Integrated services are important to facilitate provision of information on contraceptive options as well as safer conception information for PLHIV who want to have children.